Analisis Pendidikan Kewarganegaraan terhadap Peran DPRD dalam Mendorong Pemkot Tangerang Menggali Sumber PAD Baru - Aura Salsa Permana; Rosalina Bedo Jogo; Maria Seravia Sia; Ajeng Aulia Sasri (UIN Sunan Kalijaga Yogyakarta, 2025)
This study examines the role of the Regional House of Representatives (DPRD) in encouraging the Tangerang City Government to explore new sources of Local Own-Source Revenue (PAD) through the perspective of Civic Education. The analysis highlights how civic values such as democratic representation, accountability, transparency, rational policy planning, and local government responsibility shape the interaction between the legislative and executive branches in regional financial management. The DPRD’s initiative to push for innovative PAD sources reflects its commitment to strengthening fiscal independence and ensuring the sustainability of public services. Through functions of oversight, budgeting, and public representation, the DPRD motivates the local government to conduct research, benchmarking, and identification of potential economic sectors that can enhance revenue. This study concludes that the role of DPRD aligns with the core principles of Civic Education, emphasizing good governance, public participation, and regional autonomy. Strengthening PAD is essential to support improved public services, infrastructure development, and long-term regional welfare.